WORK ASPECT DIMENSION AND IT’S INFLUENCE TOWARDS EMPLOYEE’S PERFORMANCE IN HOSPITAL ORGANIZATION - Muhamad Rifa'i; Rr Nugraheni Suci Sayekti; Emilia Emilia (Unitri Press, 2017)
This research aims to know the influence of aspect dimensions working areas which include salaries, employment, promotion, supervisors, and coworkers, either simultaneously or partially. Sample research determined are purposive random sampling. The sample in this study of 53 employees non paramedics. The research of the variable is the variable which consists of salary, employment, promotion, supervisor, and co-workers. While the variable bound to the performance of the employees. Data analysis was done with descriptive analysis and inferensial with multiple linear regression analysis. Research shows aspects of work that includes salaries, employment, promotion, supervisors, co-workers and the simultaneous effect of non employee performance significantly to paramedics. The second hypothesis test indicates that the variable is only partially a significant colleague, while for variable salaries, employment, promotion, and the supervisor was not significant. While the third hypothesis suggests that the most dominant variables obtained from the standardized coefficients.